UV-A–based intervention for mitigating myopia progression via retinal dopaminergic pathways in rabbits - Christina Aritonang; Irwanto; Reni Prastyani (Jurnal Medik Veteriner, 2026)
The global rise in myopia, particularly among children and young adults, has stimulated increasing interest in environmental and light-based preventive strategies. This study investigated the protective effects of ultraviolet-A (UV-A) light exposure on myopia progression in a form-deprivation model and explored its potential mechanism via dopaminergic retinal signaling. In this experimental study, form-deprivation myopia (FDM) was induced in rabbits, which were randomly assigned to either a control group (n = 7) or a UV-A–treated group (375 nm, 12 h/day for 5 days; n = 6). Axial length, refraction, and ocular surface safety (Schirmer’s test and clinical observations) were evaluated before and after treatment. Retinal tissues were analyzed for tyrosine hydroxylase (TH) and dopamine receptors (D₁R and D₂R). Axial elongation was assessed within and between groups. UV-A–treated eyes demonstrated a shorter axial length and a greater hyperopic shift compared with controls (17.72 ± 0.14 mm vs. 23.12 ± 2.34 mm, p = 0.001; +4.58 ± 0.66 D vs. +2.64 ± 1.41 D, p = 0.001). Schirmer’s test revealed no significant differences (p = 0.40). TH and D₂R expression levels were significantly higher in the UV-A group (p = 0.013 and p = 0.009, respectively). Limitations of the study include the short experimental duration, small sample size, and the absence of a UV dose–response analysis. Overall, UV-A light exposure showed potential in inhibiting ocular axial elongation and reversing myopic shifts in a form-deprivation model, possibly through activation of retinal dopaminergic pathways, highlighting UV-A as a promising light-based intervention for myopia control.